2001
DOI: 10.1046/j.1537-2995.2001.41070917.x
|View full text |Cite
|
Sign up to set email alerts
|

WBC‐reduced platelet concentrates from pooled buffy coats in additive solution: an evaluation of in vitro and in vivo measures

Abstract: The WBC-reduced PCs conformed to specifications. These WBC-reduced PCs could be stored at least 5 days with maintenance of pH, and they gave sufficient increments after transfusion to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 17 publications
1
21
0
Order By: Relevance
“…The platelet content of the products was measured directly after production, because a previous study has shown a limited decline in platelet number during 5 days of storage. 4,23 We found significant differences with regard to pH and platelet content of the 2 PCs. The lower pH of PAS II PCs is due to a lower intrinsic pH of PAS II, lower buffering capacity, and higher lactate production.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The platelet content of the products was measured directly after production, because a previous study has shown a limited decline in platelet number during 5 days of storage. 4,23 We found significant differences with regard to pH and platelet content of the 2 PCs. The lower pH of PAS II PCs is due to a lower intrinsic pH of PAS II, lower buffering capacity, and higher lactate production.…”
Section: Discussionmentioning
confidence: 72%
“…The lower pH of PAS II PCs is due to a lower intrinsic pH of PAS II, lower buffering capacity, and higher lactate production. 23 The lower platelet content of PAS II PCs can be explained by a viscosity-related difference in the platelet distribution during centrifugation, resulting in a less efficient separation. 23 We showed that the 1-and 24-hour CCIs of PAS II PCs were lower compared with plasma PCs, with a mean difference of 19.7% and 17.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prestorage leukocyte depletion is recommended (within 6 hours after preparation if performed by filtration). [23][24][25] The three products may be stored in an additive solution to minimize the risk of transfusion reactions associated with plasma proteins and prevent the risk of transfusion-related acute lung injury. 26 Cryopreserved platelets are prepared by the freezing of platelet concentrates at À80°C within 24 hours of collection using a cryoprotectant (dimethyl sulfoxide 6% weight/ volume or glycerol 5% weight/volume).…”
Section: Platelet Concentratesmentioning
confidence: 99%
“…3 The advantages of using a PAS for platelet storage are many including more plasma to meet patient needs or to fractionate into plasma-based products, reduce red cell hemolysis from ABO incompatible plasma, and reduce other adverse effects related to plasma transfusion. 4,5 To license platelets based on poststorage radiolabeled autologous platelet viability measurements in normal subjects, the US Food and Drug Administration (FDA) requires that the lower poststorage 95% confidence limits (LCLs) for platelet recoveries are $66% and survivals are $58% of the same subject's radiolabeled fresh recoveries and survivals, respectively.…”
Section: Introductionmentioning
confidence: 99%